Migration in modern society versus multiculturality: a social-philosophical consideration - Gold, Olga; Vasalatiy, Maxym (Filosofiya osvity. Philosophy of Education, 2025)
The article examines the issue of migration in modern society and multiculturalism from a socio-philosophical perspective. The challenges facing modern society are linked to processes that are relevant both globally and in Ukraine. With the intensification of political processes, globalization and wars, the relevance of the phenomenon of migration is not diminishing. The authors consider this topic based on socio-philosophical and theoretical humanitarian methods: sociology, economics, globalization studies, cities and migration processes, referring to the approaches of the author of the term “global city” Saskia Sassen, as well as political science, law, pedagogy and philosophy of Seyla Benhabib. The doctrinal foundations of contemporary multicultural processes allow us to characterize migration processes. Migration in the world is a natural and long-term process, so all attempts to stop it are an interference in the organic processes of society. Today’s attempts by the US administration to diversify migration processes are inhumane and anti-historical. Multicultural or multi-faith education as a strategy for preserving the country’s culture and as a component of the study of the history of religions and cultures should be fundamental. We conceptualize migration as a process of perceiving another culture without losing one’s personal characteristics and traditions, but rather strengthening them and rethinking one’s previous experience – both from the side of migrants and from the side of citizens of the host country. Multiculturalism plays an important role in the struggle for equality, but it must develop a more dynamic interpretation of culture and resist unification in order to prevent gender, economic, political and religious inequality and injustice. Multicultural or polyconfessional education is proposed as a basic education for modern society as an embodiment of the strategy for preserving the country’s culture and as a component of mastering the history of religions and cultures.